2013
DOI: 10.1007/s00424-013-1324-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products impair KCa3.1- and KCa2.3-mediated vasodilatation via oxidative stress in rat mesenteric arteries

Abstract: The present study was designed to investigate the role of advanced glycation end products (AGEs) in intermediate-conductance and small-conductance Ca(2+)-activated potassium channels (KCa3.1 and KCa2.3)-mediated relaxation in rat resistance arteries and the underlying mechanism. The endothelial function of mesenteric arteries was assessed with the use of wire myography. Expression levels of KCa3.1 and KCa2.3 were measured by using Western blot. Reactive oxygen species (ROS) were measured by using dihydroethidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
5
18
0
Order By: Relevance
“…However, 48-hour incubation with metformin reversed AGE-induced downregulation of K Ca 3.1 and K Ca 2.3 (Fig. 4), which is in line with our previous study (Zhao et al, 2014). These results indicated that alterations of the K Ca channel both in protein expression and channel activity may be responsible for the beneficial effect of metformin on IK Ca -and SK Ca -mediated relaxation in vivo.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…However, 48-hour incubation with metformin reversed AGE-induced downregulation of K Ca 3.1 and K Ca 2.3 (Fig. 4), which is in line with our previous study (Zhao et al, 2014). These results indicated that alterations of the K Ca channel both in protein expression and channel activity may be responsible for the beneficial effect of metformin on IK Ca -and SK Ca -mediated relaxation in vivo.…”
supporting
confidence: 91%
“…In our previous study, diabetic rats treated with the antioxidant alpha lipoic acid, which can quench ROS, showed the restored IK Ca -and SK Ca -mediated relaxation in mesenteric arteries . Alpha lipoic acid also attenuated AGE-induced impairment of IK Ca -and SK Ca -mediated relaxation in mesenteric arteries, and reversed AGE-induced downregulation of K Ca 3.1 and K Ca 2.3 channels in cultured HUVECs (Zhao et al, 2014). These previous studies confirmed the harmful role of ROS in IK Ca -and SK Ca -mediated relaxation.…”
supporting
confidence: 73%
See 3 more Smart Citations